Doctrine of consent: examining the doctor's liability / Nurul Diyana Mohd Razali, Nurul Hafzan Ab. Aziz and Siti Fariza Jaafar. - Mohd Razali, Nurul Diyana; Ab. Aziz, Nurul Hafzan; Jaafar, Siti Fariza (2009)
This research is conducted to study the doctrine of consent: examining the doctor's liability. This research focuses on the extent of liability of a doctor who acted in the best interest of their patients despite the patient's consent before a medical treatment or procedure is carried out. Secondly, this research is conducted to analyzing the exceptional circumstances where a patient's consent is not needed for a medical treatment or procedure. Lastly, other aim of the study is to provide a clear guideline as to determine the sufficiency of information a doctor must provide to his patient. Chapter Two is on the combination of various writings made by several authors, experienced in the medical law and ethics. These reviews are important as the sources to find the extent of liability of the doctor when treating patients. Chapter Three discussed on the historical background, meaning, purpose to medical treatment. Besides that, this chapter will touch a little bit about ethical consideration which is self-determination or patients autonomy. On the other hand, in this chapter also will be discussed about the legal perspective which is when a patient had been treated without his or her consent, it will amount to negligence. Patients also can claim for breach of contract. Fourth Chapter discussed on the doctrine of informed consent and paternalism v patient autonomy. Chapter five is on the types of consent and exceptional circumstances when consent is not needed. Findings of the research and recommendation will be discussed under Chapter Six.